The association between restorative pre-clinical activities and musculoskeletal disorders - Corrocher, P. A. [UNESP]; Presoto, C. D. [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patricia Petromilli Nordi Sasso [UNESP] (Wiley-Blackwell, 2014)
Objective: To evaluate the risk of development of musculoskeletal disorders in the upper limbs of undergraduate dentistry students during the execution of pre-clinical laboratory activities based on gender, type of dental procedure and area of the mouth under treatment.Methods: Male and female undergraduate students in the second year of the Araraquara Dental School, UNESP, were enrolled in this study. Digital photographs were obtained whilst the subjects performed laboratory activities. The working postures adopted by each student were evaluated using the Rapid Upper Limb Assessment (RULA). The photos were analysed by a calibrated researcher (k = 0.89), and a final risk score was attributed to each analysed procedure (n = 354). Descriptive statistical analyses were performed, and the associations of interest were analysed by the chisquare test (P = 0.05).Results: During most of the laboratory procedures performed, the risk of developing musculoskeletal disorders was high (64.7%; - IC95%: 59.7-69.7%), with no significant association between the RULA final score and gender (chi(2) = 1.100; P = 0.577), type of dental procedure (chi(2) = 5.447, P = 0.244) and mouth area treated (chi(2) = 4.150; P = 0.126).Conclusions: The risk of developing musculoskeletal disorders was high in undergraduate dentistry students; this risk was not related to gender, type of dental procedure and region of the mouth being treated.
Keywords: occupational hazards; human engineering; dental students; musculoskeletal disorders